2007
DOI: 10.1063/1.2820386
|View full text |Cite
|
Sign up to set email alerts
|

Schottky barrier height tuning of silicide on Si1−xCx

Abstract: We have demonstrated the tuning of Schottky barrier height (SBH) of nickel silicide on silicon-carbon (Si1−xCx) by varying the carbon mole fraction, x. The SBH (for electron conduction) has been found to decrease with carbon concentration at a rate of ∼6.6meV/ (0.1% carbon). We have achieved ∼27meV drop in SBH with 0.4% carbon incorporation in Si1−xCx and shown that 1.3% carbon could lead to more than 85meV improvement. Furthermore, our results show an avenue to reduce the SBH of rare earth silicide contacts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Another possibility might be the presence of a spatially inhomogeneous Schottky barrier as proposed by Tung et al [13] for NiSi 2 , which may cause the effective barrier height to change with doping type and density. It is important to note that, regardless of the extraction method, the electron barrier-height reduction observed in this letter is much larger than the reduction predicted by Sinha et al [7], who suggested a barrier-height reduction of 65 meV per 1% C by linear extrapolation of their experimental data which were limited to a maximum carbon concentration of 0.4%. They concluded that the reduction in the electron barrier height could be explained solely by the reduction in the Si 1−x C x bandgap, which implicitly suggests that the metal Fermi level is pinned at a fixed position relative to the valence band.…”
Section: Resultscontrasting
confidence: 46%
See 1 more Smart Citation
“…Another possibility might be the presence of a spatially inhomogeneous Schottky barrier as proposed by Tung et al [13] for NiSi 2 , which may cause the effective barrier height to change with doping type and density. It is important to note that, regardless of the extraction method, the electron barrier-height reduction observed in this letter is much larger than the reduction predicted by Sinha et al [7], who suggested a barrier-height reduction of 65 meV per 1% C by linear extrapolation of their experimental data which were limited to a maximum carbon concentration of 0.4%. They concluded that the reduction in the electron barrier height could be explained solely by the reduction in the Si 1−x C x bandgap, which implicitly suggests that the metal Fermi level is pinned at a fixed position relative to the valence band.…”
Section: Resultscontrasting
confidence: 46%
“…These reports mainly focused on Manuscript formation and the structural properties of NiSi 1−y C y layers. Sinha et al [7] measured the electron barrier height at the NiSi 1−y C y /Si 1−x C x interface up to a limited carbon concentration of 0.4%. It was shown that the electron barrier height was reduced by 27 meV as a result of carbon incorporation in the underlying Si layer.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the device application, there will be a need to form high-quality ohmic or rectifying contacts to Si 1−x C x alloys. The results from several studies on this topic have been published in several recent articles [10]- [14]. These studies, which mainly focused on NiSi contacts, demonstrated that C incorporation improved the thermal stability of the silicide, while it resulted in a silicide with slightly higher resistivity.…”
Section: Introductionmentioning
confidence: 94%
“…These studies, which mainly focused on NiSi contacts, demonstrated that C incorporation improved the thermal stability of the silicide, while it resulted in a silicide with slightly higher resistivity. The Schottky barrier height, φ B of NiSi on Si 1−x C x , was also measured [14]. It was found that the electron barrier height φ Bn decreased by 27 meV for every 0.4% of C.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, achieving low contact resistance on Si 1-y C y with high substitutional carbon content (y or C sub ) is important for realizing high performance levels. Recently, it has been reported that the electron barrier height Φ B N of NiSi can be modulated linearly with C sub of 0.15, 0.28, 0.4% in Si 1-y C y films [3].…”
Section: Introductionmentioning
confidence: 99%